Efficacy of Different Gingival Displacement Materials on the Width of Gingival Sulcus Using Optical Stereomicroscope: A Comparative Analysis - Mahesh K. Rajbanshi; Manish S. Kinra; Rajashekhara B. Sharanesha; Deepti Virupakshappa; Abdullah B. Khojah; Abdulaziz A. Almakenzi; Shahad A. Almakenzi (Journal of Pharmacy and Bioallied Sciences)
Introduction: Gingival displacement is a crucial step for achieving accurate marginal adaptation in fixed partial denture prostheses. Effective gingival retraction ensures proper impression taking, particularly around the finish line. While retraction cords and retraction pastes are common methods for achieving this displacement, limited studies have directly compared their effectiveness. This study aims to evaluate and compare the efficacy of retraction cord and retraction paste in achieving lateral gingival displacement in patients requiring fixed partial denture prostheses. Method: A total of 40 patients were equally divided into two groups: Group I (retraction cord) and Group II (retraction paste). Gingival displacement was measured before and after the retraction procedure using an optical stereomicroscope with 20x magnification on diecasts. The pre and postdisplacement values were analyzed using paired t-tests to determine the significance of the displacement within each group. The lateral displacement between the two groups was compared using an independent t-test. Results: Both retraction methods demonstrated significant differences in gingival displacement before and after retraction (P < 0.001) as per the paired t-test. Group I (retraction cord) showed a greater lateral displacement (0.213 ± 0.05) compared with Group II (retraction paste, 0.129 ± 0.04), as determined by the independent t-test. Both methods achieved sufficient displacement for fixed partial denture impressions. Conclusion: While both retraction cord and retraction paste effectively achieve gingival displacement, retraction cord results in more substantial displacement. This finding suggests that retraction cord may be the preferred method when greater gingival displacement is required for optimal fixed prosthesis fabrication. However, retraction paste remains a viable option for achieving adequate displacement in most cases.